Beautiful mirrors for a pNGB Higgs - Andres, Eduardo Carlos (2016)
We consider one of the most significant deviations from the Standard Model: the forward-backward asymmetry of the b-quark measured at leptonic colliders. We investigate the possibility to solve this discrepancy by introducing new physics at the TeV scale. We focus on models where the Higgs is a pseudo Nambu-Goldstone boson of a new strongly coupled sector with a global SO(5) symmetry broken spontaneously to SO(4). Besides the usual top partners, we introduce bottom partners in the representations 16 and 4 of SO(5) and show that they can improve significantly the fit by correcting the (Formula presented.) couplings. We also estimate the corrections to the couplings at one-loop and obtain that the tree-level ones dominate and can give a reliable estimation. We find that the large shift required for (Formula presented.) leads to light custodians associated to the b-quark, similar to the top partners, as well as a rich phenomenology involving neutral interactions in the bottom-sector.